The French Revolution as a Moment of Respatialization - Middell, Matthias; Maruschke, Megan (Dialectics of the Global, 2019)
This volume examines the effects of both dimensions on the reorganization of spatial formats and spatial orders in France and in other societies. It departs from the assumption that revolutions shatter not only the political and economic old regime order at home but, in an increasingly interdependent world, also result in processes of respatialization.